Pelaksanaan Hak DPRD dalam Mengajukan Rancangan Peraturan Daerah Inisiatif di DPRD Kota Serang Provinsi Banten - Afriman Oktavianus (UNIVERSITAS PGRI YOGYAKARTA, 2025)
Abstract Submission of draft regulations may be proposed by the head of the area and can also be proposed by legislators as proposed initiative DPRD. Formulation of the problem: How does the implementation of filing draft from DPRD to draft legislation that comes from the head of the region from 2016 till 2019 in Serang City? How is the economic impact of the implementation of the draft submission from the DPRD and the draft coming from mayor of Serang City? What are the obstacles and barriers of Serang City DPRD initiative in submission the right proposal draft? What are the efforts to support the implementation of the DPRD Serang City in submitting draft initiative? Qualitative research methods with normative juridical approach and empirical juridical. The research location in the Serang City DPRD with the Legal Section of the Serang City Regional Secretariat. Conclusions: The implementation of the draft regulation on DPRD initiatives with the Mayor's proposal, in terms of quantity or amount from 2016 to 2019 as many as 30 proposals from the Mayor and as many as 21 Regional Regulations on DPRD initiatives. In the same draft quality, but there are few obstacles in the implementation of initiatives related to the formation of draft regulations implementing initiatives that DPRD be less than the maximum. The economic impact in the form of budgetary expenditures directly associated with the preparation of the budget for one academic papers on average Rp 50.000.000, - and to finance the discussion stages of starting an academic presentation, public test, parliament committee discussions, study visits and meetings plenary average for one draft Rp 250.000.000, -. Constraints and obstacles in the proposed initiative filed draft rights are affected by external factors and internal factors are: Internal factors consisting of socio-economic factors and human resources include the level of education and experience of the organization. External factors which consists of a lack of political communication between the public and DPRD with Council experts were incompetent. Efforts to support the implementation of the right to propose draft legislation initiatives include the development of the functions of DPRD, empowering legislators to improve the quality and arrangement of the institution of DPRD. Keywords: Draft Regulation, Rights Initiative, DPRD